How to Break Through the Middle-Income Trap in the Growing Vietnamese Economy: The Key Role of Management Skills and Human Resources - Hirakawa, Hitoshi; Thi Bich Ha, Nguyen; Kawai, Shin (Philippine Journal of Labor and Industrial Relations; Vol 32 No 1&2 (2012): Philippine Journal of Labor and Industrial Relations, 2021)
This paper considers the development possibility of local Vietnamese firms based on our survey. The Doi Moi policy is well known as the opening-up policy of a remarkably growing Vietnam. Since the second half of the 1990s, Vietnam has emerged as the second-best investment destination under the “China +1” scheme, and has experienced high growth rates during the latest big wave. Will this growth continue? The World Bank and the Asian Development Bank point out that in the not-too-distant future, East Asia will be creating a dominant part of the world’s wealth and will bring about a historical restoration of Asia, provided the growth of the past decade continues. On the other hand, there is a discussion that some major East Asian countries may be losing speed. This is the so-called “Middle Income Trap.” This warning has been raised for China, India, Indonesia and other countries, including Vietnam. We undertook a survey related to the management and reform potentiality of human resources of Vietnamese corporations towards overcoming issues in development. Based on our survey, we confirmed that Vietnam’s local firms are supporting the national economic development. At the same time, we will count on the potential to continue to do so. The issue remains how such potential would manifest itself.